Corporate Ownership and Control Contestability in Emerging Markets: the Case of Colombia (2007)
This paper studies the structure of voting control and block holders' contestability in Colombia for a sample of 233 non-financial listed firms during 1996-2004 period. Corporate control is characterized by high ownership concentration and block holder power, which implies low separation ratios between cash flow rights and voting rights. On average the separation ratios for the largest voting block is 0.95 while for the fourth largest shareholder it is 0.80. Corporate control is privately biased when there is direct monitoring between controlling owners and firm management. Regression results show that a more equal distribution of equity among large block holders leads to a positive effect on firm value. Contestability matters most when firm shares are liquid and highly traded on the stock market. This finding is reinforced when the probability of forming a winning coalition by the largest block decreases and when performance variables, such as market to sales ratio and return on equity, are included in the estimating equations as substitutes of firm value. In addition, our estimations provide evidence that diversion of rents is limited by block holders' contestability and there is no effective tunneling.